CiteSpace‐based visual analysis of hypothermia studies in surgical patients - Yifeng Zhou; Zhengzhong Hu; Hao Yuan; Yuelan Qin; Jin Peng (Wiley, 2023)
Abstract Aim This study was conducted to understand the research hotspots, research trends and research frontiers for hypothermia in surgical patients and provide a reference for developing effective measures to reduce the incidence of hypothermia in these patients. Design Using CiteSpace software, a visual analysis of 1288 included articles related to hypothermia in surgical patients was performed. Methods CiteSpace software is a Java application that supports knowledge research, data visualization and analysis of literature databases. The following data were retrieved: title, abstract, year, keywords, author, academic institution, journal and citations. The included literature was analysed using CiteSpace visualization software, knowledge mapping, collaborative network analysis, cluster analysis and highlighting keywords for visualization. Results A total of 1288 articles related to hypothermia in surgical patients were included, with the largest number of articles published in the United States (448), followed by in Germany (104) and China (102). The top three institutions, journals and authors were from the United States. The most common keywords were perioperative 'hypothermia', 'risk factors' and 'anesthesia'.